2003 Mixed meal effects of neprilysin inhibition - Wilson, Jessica R.; Rader, Daniel; Townsend, Raymond; Rickels, Michael (Journal of clinical and translational science, 2018)
OBJECTIVES/SPECIFIC AIMS: Test the hypothesis that neprilysin inhibition with sacubitril/valsartan will increase endogenous intact GLP-1 after a mixed meal compared with valsartan. METHODS/STUDY POPULATION: Adults 18–80 years with pre-diabetes or type 2 diabetes and elevated blood pressure. RESULTS/ANTICIPATED RESULTS: We anticipate higher intact GLP-1 area under the cure after the meal when subjects receive sacubitril/valsartan compared with valsartan. DISCUSSION/SIGNIFICANCE OF IMPACT: Neprilysin inhibition may be a target for anti-diabetes therapy by decreasing degradation of GLP-1.